Hubungan Antara Status Gizi dan Riwayat Menarche Ibu Kandung dengan Status Menarche Dini pada Siswi SD Kelas 4 – 6 di SDN 01 Nagrak Gunung Putri Bogor Periode September Tahun 2025 - Eny Irawati; Kurnia Dwi Rimandini; Miyatun Miyatun (Pusat riset dan Inovasi Nasional, 2026)
Puberty in girls is a developmental stage where sexual maturation occurs as a manifestation of reproductive ability, marked by the first menstruation (menarche), a form of primary sexual maturity in girls. The purpose of this study was to determine whether there is a relationship between nutritional status and maternal menarche history with early menarche in elementary school students in grades 4-6 at SDN 01 Nagrak Gunung Putri Bogor in September 2025. This research was a quantitative, observational analytical study using a cross-sectional approach. It was conducted at SDN 01 Nagrak Gunung Putri Bogor from August to September 2025 with a sample of 49 respondents. Univariate and bivariate data analysis used the Chi-Square Test. The results showed a relationship between nutritional status and early menarche (p-value = 0.001 and OR = 3.7) and maternal menarche history with early menarche (p-value = 0.000 and OR = 7.3). The study concluded that there is a relationship between maternal nutritional status and menarche history with early menarche. It is recommended that SDN 01 Nagrak Gunung Putri Bogor collaborate with the nearest community health center and the Health College to conduct outreach activities on reproductive health.